Identification of Golovinomyces ambrosiae Causing Powdery Mildew on Eupatorium spp. in Korea - Jun Hyuk Park; Hyeon-Dong Shin; Young-Joon Choi (Research in Plant Disease)
Powdery mildew is a common fungal disease affecting Eupatorium species, including E. japonicum, E. lindleyanum, E. makinoi var. oppositifolium, and E. tripartitum, in Korea, posing challenges for both ornamental and medicinal uses. Through morphological examination and molecular phylogenetic analyses of the internal transcribed spacer, large subunit, intergenic space rDNA regions and the glyceraldehyde-3-phosphate dehydrogenase gene, the causal pathogen was identified as Golovinomyces ambrosiae, distinct from G. circumfusus, which infects Eupatorium cannabinum in Europe. This study represents the first report of E. tripartitum infected by G. ambrosiae in Korea. The distinct separation between G. ambrosiae and G. circumfusus on Eupatorium species reflects their different geographic distributions between East Asia and Europe, likely resulting from a recent host expansion of G. ambrosiae following the introduction of Eupatorium into East Asia rather than a co-introduction of both the plant and pathogen.